2021
DOI: 10.1002/cssc.202101350
|View full text |Cite
|
Sign up to set email alerts
|

Amphilic Water‐Lean Carbon Capture Solvent Wetting Behavior through Decomposition by Stainless‐Steel Interfaces

Abstract: A combined experimental and theoretical study has been carried out on the wetting and reactivity of water-lean carbon capture solvents on the surface of common column packing materials. Paradoxically, these solvents are found to be equally able to wet hydrophobic and hydrophilic surfaces. The solvents are amphiphilic and can adapt to any interfacial environment, owing to their inherent heterogeneous (nonionic/ionic) molecular structure. Ab initio molecular dynamics indicates that these structures enable the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…This amounts to selecting a solvent with low contact angles and surface tension and a packing material with reduced degradation effects. Due to lower water content, water-lean solvents exhibit lower surface tension and consequently lower contact angles than aqueous solvents . Water-lean solvents also display comparable wetting behavior on hydrophilic (e.g., steel) and hydrophobic (e.g., plastic) surfaces, as illustrated in Figure .…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…This amounts to selecting a solvent with low contact angles and surface tension and a packing material with reduced degradation effects. Due to lower water content, water-lean solvents exhibit lower surface tension and consequently lower contact angles than aqueous solvents . Water-lean solvents also display comparable wetting behavior on hydrophilic (e.g., steel) and hydrophobic (e.g., plastic) surfaces, as illustrated in Figure .…”
Section: Methodsmentioning
confidence: 97%
“…Removing or passivating the metal interface has been shown to reduce degradation activation energies, e.g., thermal, oxidation, or hydrolysis, and increase solvent lifetime up to 50%. AIMD simulations have demonstrated that replacing the metal with plastic reduces the strength of solvent–interface interactions, which consequently reduces intermolecular and molecule–surface proton transfer processes that could promote degradation …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations